Justice to god injustice to human: assessment of the jurisdiction of Hisba in public domain - Zakariyah, Luqman (2013)
The institution of hisba in Islamic law has witnessed variations of practices in Islamic History. This is because its jurisdiction, though denotes “commanding rights and forbidding wrongs”, has not been uniquely defined. Some Muslim scholars perceived it as religious duties meant to preserve God’s rights by commanding what religiously ordained and forbidding what is religiously prohibited. In doing so, some humans’ rights may be unconsciously or deliberately infringed upon. The institution of Hisba in Nigerian Sharia saga has been clouded with mixed reaction from international community, partly because of excessive use of the mandate confined to this institution by religious dictate and state autonomy and partly from the inadequate knowledge of the concept of the institution by the external critique. This paper aims to reassess the role of hisba and its office holders in the Northern Nigerian Sharia conundrum. It will examine the interplay between rights of God and rights of human involved in the jurisdiction of hisba. The paper will conclude that justice to God‘s commandments is a core spirit of the hisba, though sometimes it leads to injustice to human."